High power maser based on 2D periodic structure and operating in the w-band frequency range - Konoplev, I; Fisher, L; Cross, A; Phelps, A; Ronald, K (2009)
Periodic structures are studied in many branches of physics including photonics, optics, electronics and physics of condensed matter, resulting in the appearance of photonic band gap materials, lasers, passive and active devices based on such lattices. Here the concept and the results of studies of a Cherenkov maser based on a surface two-dimensional periodic lattice are presented. The basic model of the maser, its parameters and the principles of operation are presented. The cavity of the maser was designed and the eigenmodes having the highest Q-factor derived. It is shown that the coupling between surface waves also known as Localised Plasmon Polaritons and volume waves (propagating waveguide modes) takes place in the vicinity of the Bragg resonance. The single mode operation of the maser is demonstrated and discussed.